2007
DOI: 10.1093/hmg/ddm296
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-potassium ATPase 1 subunit is a molecular partner of Wolframin, an endoplasmic reticulum protein involved in ER stress

Abstract: Wolfram syndrome, an autosomal recessive disorder characterized by diabetes mellitus and optic atrophy, is caused by mutations in the WFS1 gene encoding an endoplasmic reticulum (ER) membrane protein, Wolframin. Although its precise functions are unknown, Wolframin deficiency increases ER stress, impairs cell cycle progression and affects calcium homeostasis. To gain further insight into its function and identify molecular partners, we used the WFS1-C-terminal domain as bait in a yeast two-hybrid screen with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 35 publications
5
76
0
Order By: Relevance
“…S5). It has been shown that WFS1 interacts with the Na + /K + ATPase β1 subunit and the expression of WFS1 parallels that of Na + /K + ATPase β1 subunit in a variety of settings, suggesting that WFS1 may function as an ion channel or regulator of existing channels (42). Further studies on this topic would be necessary to completely understand the etiology of Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5). It has been shown that WFS1 interacts with the Na + /K + ATPase β1 subunit and the expression of WFS1 parallels that of Na + /K + ATPase β1 subunit in a variety of settings, suggesting that WFS1 may function as an ion channel or regulator of existing channels (42). Further studies on this topic would be necessary to completely understand the etiology of Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that WFS1-deficient pancreatic β cells have high baseline ER stress levels and impaired insulin synthesis and secretion. Thus, WFS1-deficient β cells are susceptible to ER stress mediated cell death (5,6,32,(40)(41)(42). The functions of WFS2 are still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane was separated from cytosolic fractions as previously described by differential centrifugation and detergent/aqueous partitioning using the Plasma Membrane Protein Extraction kit (BioVision) per the manufacturer's instructions (38). Proteins were quantified using the D C Protein Assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] Other roles, such as regulation of ER stress and protein biosynthesis, modification/ folding, have also been suggested for Wolframin. [12][13][14][15] Wolframin is an 890 amino acid oligomeric protein with a molecular mass of 100 kDa. 8,9 Although many mutations have been identified in the WFS1 gene, most affected patients carry a mutation, either insertion, deletion, nonsense or missense, in exon 8, the largest exon of WFS1.…”
Section: Introductionmentioning
confidence: 99%